The phylogenetic relationships and species richness of host-specific Dactylogyrus parasites shaped by the biogeography of Balkan cyprinids - Benovics, Michal; Desdevises, Yves; Vukić, Jasna; Šanda, Radek; Šimková, Andrea (Scientific reports, 2018)
Parasites exhibiting a high degree of host specificity are expected to be intimately associated with their hosts. Therefore, the evolution of host-specific parasites is at least partially shaped by the evolutionary history and distribution of such hosts. Gill ectoparasites of Dactylogyrus (Monogenea) are specific to cyprinid fish. In the present study, we investigated the evolutionary history of 47 Dactylogyrus species from the Balkan Peninsula, the Mediteranean region exhibiting the highest cyprinid diversity in Europe, and from central European cyprinids. Phylogenetic analyses revealed four well-supported clades of endemic and non-endemic Dactylogyrus spp. with four basal taxa. Endemic cyprinids with a limited distribution range were parasitized by endemic Dactylogyrus species, but some of them shared several Dactylogyrus species with central European cyprinids. Species delimitation analyses based on molecular data suggest that Dactylogyrus diversity is higher than that defined from morphology. Some endemic cyprinid species harboured Dactylogyrus species of different origins, this probably resulting from multiple host switching. Our results support the view that the evolution of Dactylogyrus in the Balkans has been influenced not only by the historical dispersion and distribution of their cyprinid hosts, but also by recent contacts of non-native cyprinid species with endemic cyprinid fauna in this region.
Keywords: Cyprinidae; Evolution, Molecular; Host Specificity; fylogeneze; Balkan Peninsula; hostitelská specificita; ploštěnci; Středomoří; biodiverzita; Platyhelminths; zvířata; Mediterranean Region; Animals; Balkánský poloostrov; žábry; Gills; Phylogeny; Biodiversity; molekulární evoluce